The Effectiveness of Extra Virgin Olive Oil on Blood Pressure Reduction in Obese Women - Indarwati Abdullah, Rezky Putri; Arifin Bando, Achmad Syafii; Wello, Eny Arlini Wello; R. Bamahry, Aryanti; Iskandar, Darariani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Extra virgin olive oil (EVOO), containing glycerol or subjected to hydrolysis, constitutes approximately 90-99% of the oil, primarily consisting of monounsaturated fatty acids (MUFA), with oleic acid comprising up to 80% of the total oil. This study aims to examine the influence of oleic acid in olive oil on reducing systolic blood pressure (SBP) and diastolic blood pressure (DBP). The intervention spanned 15 days, where the treatment group received EVOO, and the control group received a placebo (water), each administered twice a day at a dosage of 15 ml. Before the intervention, blood pressure was assessed with the Mann-Whitney test, while after intervention, measurements were analyzed using the Independent T-Test. Additional 15 ml Extra Virgin Olive Oil for 15 days results in significant decrease of systolic blood pressure and diastolic blood pressure compared to water only.